2023
DOI: 10.1177/08927057231155858
|View full text |Cite
|
Sign up to set email alerts
|

Process parameter tailored evaluation of FFF-fabricated carbon fibre based poly-lactic-acid composites

Abstract: Fused filament fabrication (FFF) is an Additive manufacturing technique, widely used in engineering that involves adding material layer by layer to create solid objects with complex geometry. Due to the poor mechanical performance of pure thermoplastics materials, one alternative for enhancing the mechanical qualities of FFF created thermoplastic parts is to include reinforcing material, such as carbon fibre (CF). In this work, we perform an FFF analysis of the mechanical behaviour of gyroid infilled CF based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Fiber-pull out as the major mode of damage has been previously confirmed by number of researchers. 5,80…”
Section: Resultsmentioning
confidence: 99%
“…Fiber-pull out as the major mode of damage has been previously confirmed by number of researchers. 5,80…”
Section: Resultsmentioning
confidence: 99%
“…El Magri et al 12 also noted that specific orientations, such as [0°, 15°, −15°] relative to the test bar's long axis, yielded the highest tensile properties. Similarly, Jain et al 13 observed that tensile characteristics improve as the raster angle decreases from 90° to 0°. Şık et al 14 investigated the tensile behaviour of ABS, examining various raster and build orientations through experimental and analytical methods.…”
Section: Introductionmentioning
confidence: 83%
“…15 Although they combine the greatest qualities of each distinct component, hybrids function better than their individual elements and have the potential to make prostheses for amputees. 16 To increase its structural, conductive, and thermal properties, polymers can be reinforced with substances like continuous-flax, 17 Basalt fiber, 18 SWCNTs, MWCNTs, [19][20][21] and CF. [22][23][24][25][26][27][28][29] Carboncontaining reinforcing polymer nano-composites have a significant positive impact on the physical and mechanical characteristics of specimens.…”
Section: Introductionmentioning
confidence: 99%